2021
DOI: 10.3390/molecules27010100
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Based Metal-Organic Frameworks in Drug Delivery, Cell Imaging, and Sensing

Abstract: The design and structural frameworks for targeted drug delivery of medicinal compounds and improved cell imaging have been developed with several advantages. However, metal-organic frameworks (MOFs) are supplemented tremendously for medical uses with efficient efficacy. These MOFs are considered as an absolutely new class of porous materials, extensively used in drug delivery systems, cell imaging, and detecting the analytes, especially for cancer biomarkers, due to their excellent biocompatibility, easy funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 154 publications
0
15
0
Order By: Relevance
“…These Zn(II)-based MOFs are studied as drug delivery systems due to their excellent biocompatibility, easy functionalization, high storage capacity, and excellent biodegradability [ 21 ]. In addition, considering that Zn-MOFs are developed based on a biocation, these are non-toxic species.…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%
See 1 more Smart Citation
“…These Zn(II)-based MOFs are studied as drug delivery systems due to their excellent biocompatibility, easy functionalization, high storage capacity, and excellent biodegradability [ 21 ]. In addition, considering that Zn-MOFs are developed based on a biocation, these are non-toxic species.…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%
“…Among these materials, metal–organic frameworks (MOFs) represent a special class that provide the advantage of both ultrahigh porosity and specific surface area, high thermal stability, adaptable surface chemistry, adjustable crystal structure and morphology, open metal sites and robustness [ 18 ]. The current limitations of Zn-based MOFs in comparison with others Zn-CBCPs come from the fact that is difficult to control the morphology and structure [ 18 ] and to create a mixture either of organic linkers, carboxylate and N-donor ligand or of cations Zn(II) and another cation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also detect the presence of the drug in the MOFs after the adsorption process with the help of FT-IR. They concluded on the basis of these results that the prepared MOFs could be used for the removal of amodiaquine from wastewater Rashda Safdar Ali, Hongmin Meng and Zhaohui Li [45], also reported some zinc-based metal-organic frameworks in drug delivery, cell imaging and sensing on the basis of the fact that zinc is a low-toxic transition metal cation, zinc-based MOFs used as drug carriers in the biological system [46], used in dermatology as a skin moisturizing agent with astringent, antibacterial agent and it has anti-inflammatory properties [47,48]. They suggested that Zn-metal centres in MOFs have been created by improving drug delivery and these Zn-based MOFs have been appeared to be safe as it was elucidated by different cytotoxicity assays for targeted drug delivery.…”
Section: Synthesis and Applicationmentioning
confidence: 95%
“… 126 Compared with traditional organic and inorganic drug delivery systems, drug carriers based on MOFs have higher drug load and the possibility of chemical functionalization, which can enhance drug affinity. 127 , 128 They are widely used in biological fields such as drug delivery and biomarker detection due to their large pore volume, pore size and surface area, as well as adjustable surface functionality, and the metal-ligand bond strength is determined by the properties of metal ions and ligands, and is also the key to determining the hydrothermal stability of MOFs. 127 , 129 , 130 Recently, Yao et al 131 prepared a Zn-MOF encapsulated methacrylated hyaluronic acid (MeHA) microneedles (MNs) array.…”
Section: Biological Nanomaterials For Skin Wound Repairmentioning
confidence: 99%